Efektifitas Palvic Rocking Exercise dan Endorphin Massage Terhadap Nyeri Persalinan Pada Ibu Bersalin Kala 1 Fase Aktif Di Puskesmas Banyuglugur Kabupaten Situbondo - Kholid Fauzi, Ahmad; Hasanah, Faridatul; Rozi, Fahrur (LPPM STIKES HUSADA JOMBANG, 2023)
Introduction: The process of childbirth occurs through four stages of labor, namely the first stage, which is the stage that lasts from regular uterine contractions to complete cervical dilatation. The second stage lasts from complete cervical dilatation until the fetus is born. Stage III lasts from the time the fetus is born until the placenta is born. The fourth stage lasts about two hours after the placenta is born. The delivery process can cause pain in the mother who gave birth. Labor pain, as a contraction of the myometrium which is a physiological process with different intensity in each individual. Palvic Rocking Exercise is an effective form of exercise that can strengthen the abdominal and lumbar muscles and reduce pressure on the waist by moving the fetus forward from the mother's waist so as to reduce labor pain. Endophine Massage is a light touch and massage technique that is quite important to give to pregnant women, from the time leading up to the time of delivery, this is because massage stimulates the body to release endophin compounds which are painkillers and can create a feeling of comfort. Methods: This research is a quasi-experimental study with a Two Group Pretest Posttest design. The sample in this study was 30 people and divided into 2 groups of research subjects using consecutive sampling. Data were analyzed using independent t test. Results and Discussion: The statistical test resulted in no significant difference in the p value (> 0.263) which indicated that there was no difference in the scale of labor pain between the Palvic Rocking Exercise and the Endophin Massage. Conclusion: There is no difference in labor pain scale between Palvic Rocking Exercise and Endophin Massage.